2014
DOI: 10.1007/s11356-014-3497-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of anthelmintic drugs (fenbendazole and flubendazole) to aquatic organisms

Abstract: Flubendazole (FLU) and fenbendazole (FEN) belong to benzimidazoles—pharmaceuticals widely used in veterinary and human medicine for the treatment of intestinal parasites as well as for the treatment of systemic worm infections. In recent years, usage of these drugs increased, which resulted in a larger contamination of the environment and possible negative effects on biota. Hence, in our research, we investigated an aquatic ecotoxicity of these pharmaceuticals towards: marine bacteria (Vibrio fischeri), green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…For this reason ABZ as well as other anthelmintics have been classified as emerging environmental contaminants (Wagil et al, 2015). The negative environmental effects of benzimidazole drugs have been described many times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason ABZ as well as other anthelmintics have been classified as emerging environmental contaminants (Wagil et al, 2015). The negative environmental effects of benzimidazole drugs have been described many times.…”
Section: Introductionmentioning
confidence: 99%
“…The negative environmental effects of benzimidazole drugs have been described many times. Comprehensive studies, for example, have revealed the toxicity of benzimidazoles to different aquatic organisms (Wagil et al, 2015) (Bunduschuh et al, 2016). ABZ can also severely affect earthworms living in soil (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Wagil et al (2015) evaluated the ecotoxicity of two anthelmintic drugs (fenbendazole–FEN and flubendazole–FLU) towards different aquatic organisms: luminescent marine bacteria ( Vibrio fischeri ), lumnic inicellular green algae ( Scenedesmus vacuolatus ), duckweed ( Lemna minor ) and crustacean ( Daphnia magna ). Daphnia magna appeared to be the most sensitive organism with EC 50 values for FLU and FEN of 45 μg/L and 19 μg/L, respectively.…”
Section: Pharmacuetical Contaminantsmentioning
confidence: 99%
“…Gastrointestinal nematodes (GINs) represent an important disease within livestock's´ productive systems. The generalization and overuses of therapeutic drugs have prompted a high prevalence of multi-drug resistances within target parasitic population impacting small ruminant production systems (Torres-Acosta and Hoste, 2008), animal health (Jackson et al, 2012;Kaplan and Vidyashankar, 2012;Waller, 2007), persuading environmental risks (Beynon, 2012;Horvat et al, 2012;Wagil et al, 2015), and consumers concerns (Whelan et al, 2012). Resistances against the major families of anthelmintics represent a worldwide phenomenon to overcome to preserve the effectiveness of the anthelmintics (AHs).…”
Section: Introductionmentioning
confidence: 99%